2013
DOI: 10.1038/bjc.2013.537
|View full text |Cite
|
Sign up to set email alerts
|

The novel toluidine sulphonamide EL102 shows pre-clinical in vitro and in vivo activity against prostate cancer and circumvents MDR1 resistance

Abstract: Background:Taxanes are routinely used for the treatment of prostate cancer, however the majority of patients eventually develop resistance. We investigated the potential efficacy of EL102, a novel toluidine sulphonamide, in pre-clinical models of prostate cancer.Methods:The effect of EL102 and/or docetaxel on PC-3, DU145, 22Rv1 and CWR22 prostate cancer cells was assessed using cell viability, cell cycle analysis and PARP cleavage assays. Tubulin polymerisation and immunofluorescence assays were used to assess… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 33 publications
1
3
0
Order By: Relevance
“…The present study supported the results published by Galal, Abdelaziz, Toner, and Liu [19,32,41,42]. It was reported that the synthesized compounds mediated their anticancer action through the binding to the colchicine-binding site of tubulin and exert part of their action through arresting cell division at the G2/M phase.…”
Section: Ic50supporting
confidence: 92%
“…The present study supported the results published by Galal, Abdelaziz, Toner, and Liu [19,32,41,42]. It was reported that the synthesized compounds mediated their anticancer action through the binding to the colchicine-binding site of tubulin and exert part of their action through arresting cell division at the G2/M phase.…”
Section: Ic50supporting
confidence: 92%
“…The results demonstrated that Sorcin silencing increased the intracellular concentration of Rhod-123 and decreased the expression of P-gp to reverse the drug resistance of tumor cells. MDR1, LRP and MRP1 are the most common membrane transporters that efflux drugs out of cells and are frequently found to be overexpressed in the drug resistant environment (13)(14)(15). The expression of these proteins in A549/DDP cells prior to and following Sorcin silencing was investigated.…”
Section: Discussionmentioning
confidence: 99%
“…However, inhibiting MDR1 directly may not be the method to overcome drug efflux and resistance to taxanes. Despite positive in vitro and in vivo studies [ 163 , 306 , 319 , 320 , 321 ], clinically, MDR1 inhibitors have not been successful. This could be due to the increased toxicity of taxanes, increased levels of supplementary drug transporters, or upregulation of other resistance mechanisms.…”
Section: Taxane Resistance In Prostate Cancermentioning
confidence: 99%